Habitat preferences of a secretive marsh bird using a man-made habitat: the case of Little Bittern (Ixobrychus minutus minutus) - A. Flis; P. Skórka; W. Król (The European Zoological Journal, 2024)
Many marsh birds, like bitterns or rails, are endangered species inhabiting only natural habitats and dependent exclusively on different types of emergent vegetation. In a changing environment, some of these habitat specialists are becoming more flexible, shifting their preferences by colonizing man-made habitats. We studied habitat selection by Little Bitterns (Ixobrychus minutus minutus) breeding in a fishpond landscape in south-eastern Poland. Applying a large-scale research approach, we examined several habitat features in order to predict the presence of the Little Bittern from a direct comparison of areas with and without breeding birds. Partial least squares (PLS) regression identified two components of several variables that explained 53% of the variation in the presence of the Little Bittern in a fishpond habitat. The occurrence of the Little Bittern was limited to high-quality patches of emergent vegetation, the height, width and area of which were all significantly greater in the area with breeding birds than in unoccupied patches. Patches with a highly variable edge line in the form of fringes or indentations were less favoured. An optimal water level throughout the breeding season was crucial for nest-site selection and ensured access to food. The heterogeneity of the pond dykes and pond canals positively predicted the presence of the Little Bittern by creating potential nesting or foraging sites. Interestingly, the proportion of bulrushes (Typha spp.) in the emergent vegetation patches had a negative effect on the presence of the Little Bittern. The main threat to this habitat‐sensitive species was the cutting of perennial emergent vegetation, in particular the Common Reed (Phragmites australis).